2021
DOI: 10.5194/egusphere-egu21-821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local time and longitudinal differences in the occurrence frequency of ionospheric EMIC waves during magnetic storm periods

Abstract: <div><span>The spatial and temporal distributions of ionospheric electromagnetic ion cyclotron (EMIC) waves during magnetic storms from 2014 to 2018 were studied using Swarm observations. Ionospheric EMIC waves preferably occurred during storms and their recovery phases at subauroral regions within an average magnetic latitude of 40°-55°. There were more wave events during more intense and longer period storms. However, the correlation between event number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The rate is higher at the equinoxes, which might be related to the higher magnetic activity during these seasons. The occurrence rate of magnetospheric EMIC waves increases during higher magnetic activities (Erlandson & Ukhorskiy, 2001; Kim, Shiokawa, Park, Miyoshi, Stolle et al., 2021; Wang et al., 2021). To further validate this result, Figure 9 shows the distribution of large‐spatial‐scale transverse waves and parallel waves with magnetic local time and magnetic latitude under two different dipole tilt (DPT) angle conditions (|DPT| < 10° and |DPT| ≥ 10°).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The rate is higher at the equinoxes, which might be related to the higher magnetic activity during these seasons. The occurrence rate of magnetospheric EMIC waves increases during higher magnetic activities (Erlandson & Ukhorskiy, 2001; Kim, Shiokawa, Park, Miyoshi, Stolle et al., 2021; Wang et al., 2021). To further validate this result, Figure 9 shows the distribution of large‐spatial‐scale transverse waves and parallel waves with magnetic local time and magnetic latitude under two different dipole tilt (DPT) angle conditions (|DPT| < 10° and |DPT| ≥ 10°).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. (2021) studied the spatio‐temporal distribution characteristics of EMIC waves during magnetic storms using observational data from the Swarm satellites over the years 2014–2018. They showed that the peak occurrence rate of the storm‐time EMIC waves was approximately 4%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations